Sistem Pendukung Keputusan Pengembangan Pariwisata Alam Kawasan Plawangan – Turgo Menggunakan Model AHP dan TOPSIS - Marutha, I Gede Putu; Sutayasa, Kadek Agus (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
The development of the nature tourism area is very much needed for the success of the village fund program, which is planned to increase the income of the people around the attractions and nature conservation. In addition to the level of community participation there are several natural attractions in Bukit Turgo, lacking assistance in the form of road improvements, lighting, access in and out and so on. With the limited village funds, the development of natural tourism objects around Turgo Hill cannot be done simultaneously. The selection of tourism objects which should receive development funds for the first time, must have the best evaluation criteria among other attractions. This study aims to determine the natural tourism objects that receive village funding assistance, for the development of tourism in these attractions. Participation in the use of the community in the development of the Bukit Turgo - Plawangan tourism object, based on the principles of ecotourism and formulating a strategy for the development of the Plawangan-Turgo natural tourism object to be of particular benefit to the community. To make the selection process through the ranking process used an approach to the Decision Support System model, using the AHP and TOPSIS methods. The weighting method in AHP is used to determine the criteria and sub-criteria weights according to the decision maker, in this study the community is represented by the village head. The TOPSIS method is used to rank the best alternative from a number of alternatives. The test results show that the system can provide a ranking sequence for tourism objects correctly according to manual calculations. The results of the comparison of existing criteria also show the Landscape (Landscape) on Turgo Hill became the first choice and the Japanese cave became the last choice.